Dysregulation of Micro RNA-155 as a Biomarker in Iraqi Patients with Prostate Cancer - Al-saffar, Jinan MJ (Iraqi Journal of Science, 2021)
Chronic inflammation can induce proliferative events and posttranslational DNA modifications in prostate tissues through oxidative stress. The miR-155 expression is abnormally increased in tumors. Therefore, this study aims to explore the clinical significance of serum TNF-α and IL-1α as well as miR-155 expression in prostate cancer (PC) patients.A total of 50 blood samples from patients diagnosed with prostate cancer were collected from the Oncology Department, Baghdad Teaching Hospital, along with samples from 50 healthy volunteers. Serum TNF-α and IL-1α levels in Iraqi males with prostate cancer were estimated by using enzyme-linked immunosorbentassay (ELISA). The total RNA was extracted from all subjects and converted to cDNA using Stem-Loop technique and the expression was measured by real-time PCR (RT-PCR) using SYBR Green with specific primers. The results showed that serum TNF-α and IL-1α levels were significantly higher in the clinical stage of tumor node metastasis (TNM) as compared to those in the control (p<0.05). The miR- 155 level was significantly elevated in the patients compared with the control (p<0.05), being positively correlated with advanced stages. It is concluded that circulating miR-155 could act as a promising marker for the diagnosis and prognosis of PC.